The management and tourism of protected areas in Budapest - Tenk, A. (Ye.A.Buketov Karaganda State University Publ., 2015)
Around 5 % of the territory of Budapest is under protection by the Duna-Ipoly National Park, and 1,6 % is protected by the Budapest Municipality. In these protected habitats several Pannon endemic species live, some species are threatened according to the IUCN Red List of Threatened Species. Presently, there are not enough financial sources to protect and manage these areas in Budapest. Therefore, the political leaders of local governments, conservationist NGOs and local communities debate about how to manage these protected areas. Furthermore, it is frequently asked why it is important to reserve these fragmented and often small areas in an urbanized area, like Budapest. The national park and the NGOs have more professional skills and tender possibilities (LIFE+, Environment and Energy Operative Program) to manage the protected areas than the local governments or Budapest Municipality, because the latter organizations receive financial resources only from the central government budget and from local taxes. Moreover thanks to protection and to professional management, we can use geo- and biodiversity as tourist attractions, which can make a profit for the proprietor.
Будапешт қалалық қорықтарының менеджменті мен туризмі
Менеджмент и туризм городскиx заповедников Будапешта
Keywords: urban tourism; nature conservation; city development; public administration